Pembangunan metrik penilaian universiti lestari - Abdul Shakur, Elia Syarafina (2013)
Sustainable development means what we owned today will be owned by the future generations. It has been introduced and considered in education sector. The concept of sustainable universities had been implemented by international universities in 1970. However, it is a transformation and a challenge to local universities in moving towards sustainability. The main challenge is that no comprehensive evaluation metric for measuring the level of sustainability in local university. The main objective of this research is to develop a comprehensive Sustainable University Evaluation Metric for Universiti Teknologi Malaysia (UTM). To achieve the mentioned objective, there are four stages have been conducted. First, a search of literature review to identify the concepts, models and metrics of sustainable university. Second, the characteristics of sustainable university are identified. Third, identification of the appropriate characteristics to develop evaluation metric for sustainable university. Finally, interviews with expert were conducted to verify the evaluation metrics which involved two phases. In the first phase, an expert interview was conducted to obtain information to improve and to verify sub-elements and the characteristics of the proposed Evaluation Metric for Sustainable University. In the second phase, expert interview was repeated to gain comments and suggestions to improve the evaluation metric. This analysis was conducted by using qualitative methods known as content analysis. The outputs of the study are sub elements, characteristics of sustainable university based on elements of environment, social and economic, and a comprehensive evaluation metric for the UTM. The evaluation metric will serve as guideline to monitor and evaluate the performance of sustainable initiatives in UTM and other local universities.